2018
DOI: 10.1007/s13197-018-3141-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of physicochemical indexes, amino acids, phenolic compounds and volatile compounds in bog bilberry juice fermented by Lactobacillus plantarum under different pH conditions

Abstract: This study aimed to investigate the effect of strains on quality improvement of bog bilberry juice. Bog bilberry juice with different pH conditions was fermented by B7 or C8-1 strain. Physicochemical index, amino acids, phenolic compounds, and volatiles of these fermented juices were compared. Results indicated that strains preferred to metabolize malic acid and reducing sugar in non-pH-adjusted juice (NJ, pH 2.65), whereas quinic and citric acids were largely consumed in pH-adjusted juice (AJ, pH 3.50). Shiki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
34
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 35 publications
8
34
2
Order By: Relevance
“…Among the production processes, lactic acid fermentation is considered as a simple and valuable biotechnology for enhancing those features of fruits (Di Cagno et al., 2013; Swain et al., 2014; Szutowska, 2020). In this regard, the effect of lactic acid fermentation on the texture, color, and composition of many kinds of fruits has been well studied (Di Cagno et al., 2011; Chen et al., 2019; Chen, Ouyang, et al., 2019; Filannino et al., 2013; Li et al., 2021; Muhialdin et al., 2020, 2021; Peng et al., 2021; Ricci et al., 2018; Wei et al., 2018). However, the literatures concerning the lactic acid fermentation of goji berry fruits are scarce (Liu et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Among the production processes, lactic acid fermentation is considered as a simple and valuable biotechnology for enhancing those features of fruits (Di Cagno et al., 2013; Swain et al., 2014; Szutowska, 2020). In this regard, the effect of lactic acid fermentation on the texture, color, and composition of many kinds of fruits has been well studied (Di Cagno et al., 2011; Chen et al., 2019; Chen, Ouyang, et al., 2019; Filannino et al., 2013; Li et al., 2021; Muhialdin et al., 2020, 2021; Peng et al., 2021; Ricci et al., 2018; Wei et al., 2018). However, the literatures concerning the lactic acid fermentation of goji berry fruits are scarce (Liu et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The adjustment of pH could alter the composition of anthocyanins, leading to a change on the appearance of bog bilberry juice. Recent studies showed that L. plantarums strains could consume malic acid to produce lactic acid in juices with pH < 3.0 made from bog bilberry and sea buckthorn (pH < 3.0) [25,28]. To the best of the authors’ knowledge, there are no published studies to investigate the growth and metabolism of LAB in bog bilberry juice or to evaluate the effect of LAB on the alteration of chemical constituents in bog bilberry juice.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the sugar:acid ratio of L. paracasei group increased continuously the first 12 hr, so it is worth considering extending the fermentation time to investigate the variation trend of sugar:acid ratio. Malic acid has a harsh mouthfeel, but lactic acid fermentation can convert malic acid into lactic acid, thus significantly reducing the harshness of fruit juice (Wei et al, ). From this point of view, our FOGJ may be more organoleptically acceptable to consumers.…”
Section: Resultsmentioning
confidence: 99%